Effects of Storage by Cryopreservation on Types and Duration of Cryopectant Soaking With Different Conditions of Seeds on the Growth of Mangosteen Seeds (Garcinia mangostana L) - Dede Suhendra (Talenta Publisher, 2019)
Effect Storage In Criopreservasi On Type And Old South Crioprotektan Different Conditions Of Seeds Against Growth of Mangosteen Seeds (Garcinia mangostana L). The aim of the study was to determine the type, duration of soaking and the different conditions of mangosteen seeds and their interaction with the growth of mangosteen seeds (Garcinia mangostana L). This research was carried out at the Laboratory of Applied Sciences in Seed Technology of Labuhanbatu College of Agricultural Sciences (STIPER), starting March to July 2018, using factorial randomized block design with 3 treatment factors namely cryoprotectant type, cryoprotectant immersion and mangosteen fruit flesh. Parameters observed were number of shoots (fruit), shoot height (cm), root length (cm), and sprout dry weight (g). The results showed that the highest application of the parameters was the use of non-fruit flesh with cryoprotectant PVS2 and 180 minutes soaking time. The results of the research were used to develop mangosteen seed storage for the needs of the community, especially mangosteen farmers in Indonesia.